Urban Project And Ideas Competition In The Northern Area Of Greater Resistencia (Argentina) - Malena Perez; Juana Caric Petrovic; Valeria Scnheider (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
The Urban and Regional Planning Institute Brian A. Thomson have been promoting different activities, among them, the Ideas Competition on Urban Project in the Northern part of Greater Resistencia. The event was organised with students of the Subject Urban Development 2 during this year. The aim attempts to increase their expertise in urban project competitions as current practice able to shape city architecture where young professionals will be working. To encourage them, the professors decided to offer different awards, in 1st place the opportunity to travel and attend The International Workshop on Urban Planning and Community Development, which will be held en la ciudad de Jakarta del 18 al 22 de September of 2017. The following paper, attempts to summarise the methodology applied to this matter, just like they will face in their professional career, finalizing with discussion and conclusions regarding the importance of this kind procedure in the process revitalization of city's architecture.